2020
DOI: 10.1371/journal.ppat.1008849
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 imparts BRCAness by impairing homologous recombination repair in Epstein-Barr virus-transformed B lymphocytes

Abstract: Epstein-Barr virus (EBV) causes lymphomas and epithelial cell cancers. Though generally silent in B lymphocytes, this widely prevalent virus can cause endemic Burkitt lymphoma and post-transplant lymphoproliferative disorders/lymphomas in immunocompromised hosts. By learning how EBV breaches barriers to cell proliferation, we hope to undermine those strategies to treat EBV lymphomas and potentially other cancers. We had previously found that EBV, through activation of cellular STAT3 prevents phosphorylation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 57 publications
1
11
0
Order By: Relevance
“…We also found an association between high levels of pTyr705-Stat3 and BRCA2 mutation, which is more common in ER-positive luminal B tumors ( 39 ). Moreover, consistent with our findings, pTyr705-Stat3 has been reported recently to disrupt CHK1 phosphorylation, thereby impairing BRCA2-mediated RAD51 recruitment for homologous recombination repair of double-strand DNA breaks ( 40 ).…”
Section: Discussionsupporting
confidence: 92%
“…We also found an association between high levels of pTyr705-Stat3 and BRCA2 mutation, which is more common in ER-positive luminal B tumors ( 39 ). Moreover, consistent with our findings, pTyr705-Stat3 has been reported recently to disrupt CHK1 phosphorylation, thereby impairing BRCA2-mediated RAD51 recruitment for homologous recombination repair of double-strand DNA breaks ( 40 ).…”
Section: Discussionsupporting
confidence: 92%
“…More importantly, we further revealed that the downregulation of CFHR3 increased HCC cell growth and metastasis, which was suppressed by the STAT3 inhibitor, S3I-201. As known to us, phosphorylated STAT3 constitutes an essential pathway that regulates the signaling of miscellaneous biological activities including drug resistance, cell metastasis as well as cell proliferation [ 34 , 35 ]. In our study, we confirm that the phosphorylated STAT3 induced by CFHR3 downregulation suppressed p53 expression to promote HCC progression.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, histidine triad nucleotide binding protein 1 (HINT1) encodes a protein that hydrolyses purine nucleotide phosphoramidate substrates and is mostly believed to be a tumour suppressor in multiple cancer types [61][62][63]. Another finding in malignant plasma cells is the involvement of genes (MDM2, CCND2, CDK6, STAT3, HLA-F, HLA-B, HLA-C, HLA-E, JUN, PSMC1) in Epstein-Barr virus (EBV) infection and viral carcinogenesis [64][65][66][67]. Further in-depth studies of their roles in EBV infection and plasma cell proliferation are needed in the future.…”
Section: Discussionmentioning
confidence: 99%